O paradoxo a partir da teoria dos blocos semânticos : língua, dicionário e história - Machado, Julio Cesar (Universidade Federal de São Carlos, 2015)
In general, the idea of this work is to investigate the paradox, our object, by a linguistic and argumentative way, from the Theory of Semantic blocks (TBS). And specifically, for this, we adopted as main methods, two gestures: the relationship between linguistic elements as analysis condition, on the one hand, and the interdependence of its structure and significance, on the other hand, both in the non- use (language) and the use of language (enunciation). This second method of interdependence, when applied to our object, the paradox, becomes our first central hypothesis, the possibility of semantic paradox: the strange and difficult linguisticargumentative consideration of opposite significances, but in the interdependent state. And in this context we will also develop a second central hypothesis: the argumentative cube, while theoretical actualization of the argumentative square (the basic theoretical framework of our theory). Organizationally, the resourcefulness of this work will be carrying out in several specific strands, distributed throughout the chapters, namely: theory / paradox (divided into "Argumentation in the Language" / paradox, at first, and "Theory of Semantic Blocks "/ paradox, in a second stage); discours / paradox; dictionaries / paradox; "Historic Semantics of Enunciation" / paradox; relationship between languages / paradox and anteriority / paradox. In addition to these relational axes established to better observe our object, the paradox, and defend our hypothesis, the semantic paradox, we elected as central corpora, a group of dictionaries in which we can catch "which is said to be" a paradox and "as they say "a paradox to ponder" which means "a paradox. These dictionaries are divided into main corpus: Dictionnaire Historique de langue francaise, and and secondary corpora : Enciclopédia e Dicionário ilustrado, Kokugo Ziten e Dicionário Houaiss da Língua Portuguesa, among others.

L'idée de ce travail est d'étudier le paradoxe d’une façon linguistique et argumentatif, à partir de la Théorie des Blocs Sémantiques (TBS). Et précisément pour cela, nous prenderons comme principales méthodologies deux gestes : la relation entre des éléments linguistiques comme condition d'analyse, et l'interdépendance entre la structure et sa significance, à partir tant par le champ du non-usage (langue), comme du champ d’usage de la langue (l'énonciation). Cette seconde méthode d'interdépendance, lorsqu'elle est appliquée à notre objet (le paradoxe) constitue mon premier hypothèse centrale : la possibilité du paradoxe sémantique : la considération linguistique-argumentative de signifiances opposées, mais dans un état d’interdépendance. Et dans ce contexte nous allons développer aussi une deuxième hipothèse centrale: le cube argumentatif, tandis que une atualization théorique du carré argumentatif (le construct théorique base dans notre théorie). Sur le plan organisationnel, l'ingéniosité de ce travail sera effectuer dans plusieurs axes spécifiques, répartis sur plusieurs chapitres: la théorie/paradoxe (premièrement «Argumentation dans la langue»/paradoxe, et deuxièmement «Théorie des blocs sémantiques»/paradoxe); discours/paradoxe; dictionnaires/paradoxe; «Sémantique Historiques de l'Énonciation» / paradoxe; relation entre des langues / paradoxe et antétriorité / paradoxe. En plus de ces axes relationnels mis en place pour mieux observer notre objet (le paradoxe) et de défendre mon hypothèse du paradoxe sémantique, je formerai un corpus à partir d’un groupe de dictionnaires dans lesquels appairassent « ce qui ce dit être » un paradoxe et « comment est-ce qu’» un paradoxe ce dit, afin de reflechir sur ce « que signifie un paradoxe ». Les dictionnaires sont divisés en corpus principal: Dictionnaire Historique de langue francaise, et corpora secondaire: Enciclopédia e Dicionário ilustrado, Kokugo Ziten e Dicionário Houaiss da Língua Portuguesa, parmi d’autres.
The paradox as from the theory of semantic blocks : language, dictionary and history
Le paradoxe a partir de la théorie des blocs sémantiques : langue, dictionnaires et histoire
Keywords: Semântica; Semântica argumentativa; Paradoxo; Dicionários; História; Argument; Semantics; Paradox; Dictionary; History; Argumentation; Sémantique; Paradoxe; Dictionnaire; Histoire; LINGUISTICA, LETRAS E ARTES::LINGUISTICA